A Study of Environmental Degradation in Turkey and its Relationship to Oil Prices and Financial Strategies: Novel Findings in Context of Energy Transition - Habeşoğlu, Osman; Samour, Ahmed; Tursoy, Turgut; Ahmadi, Mohsen; Abdullah, Lazim; Othman, Mahmod (Frontiers in Environmental Science, 2022)
In the current empirical literature, the possible influence of oil price on environmental degradation through fiscal policy instruments has been ignored. To address this gap, this study explores the influence of oil price on the environmental degradation in Turkey through fiscal policy instruments, using a novel methodology of bootstrap ARDL approach. The FMOLS, CCR, DOLS, and ARDL models are used to examine the long-run linkage among the tested variables. The findings from estimating models demonstrated that government expenditures affected positively environmental degradation in Turkey. In contrast, the taxation revenues affected negatively environmental degradation. Furthermore, the empirical outcomes affirm that prices of oil have a powerful effect on the levels of Turkey’s environmental pollution through taxation revenues, energy, and GDP factors. The study suggests that the Turkish policymakers should design policies to avoid any undesirable impacts of the spillover effects of the oil price on the environment using fiscal policy channels. In this sense, the government in Turkey should design a framework that includes financial incentives such as low taxation rates on green energy investment. In addition, the policy markets in Turkey should start to use the carbon taxes policy, which is one of the most efficient tools to reduce the level of environmental pollution.